2002
DOI: 10.4049/jimmunol.169.6.3250
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxins 13 and 7 Function at Distinct Steps During Phagocytosis

Abstract: The phagosome is a dynamic organelle that undergoes progressive changes to acquire the machinery required to kill and degrade internalized foreign particles. This maturation process involves sequential interaction of newly formed phagosomes with several components of the endocytic pathway. The proteins that mediate the ordered fusion of endosomes and lysosomes with the phagosome are not known. In this study, we investigated the possible role of syntaxins present in the endo/lysosomal pathway in directing phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 33 publications
(27 reference statements)
3
63
1
Order By: Relevance
“…The identification of trans-complexes between V0 domains in adjacent membranes showing the same dependence on inhibitors and activators as the fusion process itself led to the proposal that, after SNARE mediated docking, these transcomplexes promote the mixing of the lipid bilayers by virtue of the highly hydrophobic proteolipid subunits (50). Interestingly, our results confirmed that the SNARE protein syntaxin 7 accumulates in late phagosomes (51), supporting the notion that this enrichment occurs specifically in detergent-insoluble parts of the membrane. The role of the lipid environment as regulator of V-ATPase activity was addressed by Lafoucade and colleagues who concluded that the DRMs association increased the pump activity by promoting V1-V0 coupling (52).…”
Section: Discussionsupporting
confidence: 77%
“…The identification of trans-complexes between V0 domains in adjacent membranes showing the same dependence on inhibitors and activators as the fusion process itself led to the proposal that, after SNARE mediated docking, these transcomplexes promote the mixing of the lipid bilayers by virtue of the highly hydrophobic proteolipid subunits (50). Interestingly, our results confirmed that the SNARE protein syntaxin 7 accumulates in late phagosomes (51), supporting the notion that this enrichment occurs specifically in detergent-insoluble parts of the membrane. The role of the lipid environment as regulator of V-ATPase activity was addressed by Lafoucade and colleagues who concluded that the DRMs association increased the pump activity by promoting V1-V0 coupling (52).…”
Section: Discussionsupporting
confidence: 77%
“…VAMP-8 has been reported to form complex with Syn-7, Syn-8, and Vti1b, which mediates homotypic fusion of early and late endosomes (15,17,18). As reported previously, Syn-7 was recruited to phagosomes in macrophages (31). Interestingly, this same set of Syn-7-containing Q-SNAREs (Syn-7-Syn-8-Vti1b) also partners with VAMP-7 for mediating heterotypic fusion of the late endosomes and lysosomes (18).…”
Section: Discussionmentioning
confidence: 59%
“…Candidates are, for example, STX7 which has been found to reside in late endosomes and to participate in the process of phagocytosis [20]; alternatively or in addition STX18, which has been implicated in endoplasmic reticulum-mediated phagocytosis in J774 macrophages [21]. Furthermore, STX4 and STX6, which are regulated in LPS activated RAW264.7 macrophages, have been described to regulate the exocytosis of TNF [22,23] in these cells.…”
Section: Discussionmentioning
confidence: 99%